Liability for damage caused by unsafe innovative food – a legal perspective - Sokołowski, Łukasz Mikołaj (Przegląd Prawa Rolnego, 2020)
The subject of the considerations presented in the article are issues related to the liability for placing unsafe innovative food on the market. They are aimed at answering the question of whether the tort liability regime based on the risk principle meets the requirements of the modern agri-food sector and provides effective protection of consumer’s health and life against threats that may result from product innovations. The adoption of legal solutions providing for producer’s strict liability for an unsafe product must be assessed positively. They facilitate the consumer’s ability to seek redress for damage caused by an unsafe product. Unfortunately, these regulations do not take into account fully the specific nature of food, especially innovative food, limiting the possibility of redressing damage caused by this type of food.